Kinematics of free-floating robots revisited - Dulęba, Ignacy (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, a decomposed expression for the kinematics of a free-floating robot with rotational joints is derived in detail. Some mathematical conditions on invertibility of a matrix used in a definition of the generalized Jacobian matrix are derived and proved for a general robot and for a planar robot (an n-pendulum). For the n-pendulum, closed-form kinematics are given. A comparison of the resulting kinematic equations for the simplest free-floating robot (a planar 2-pendulum), with the simplest mobile robot (a unicycle) is presented. Being an extended version of (Dulęba, 1996), this paper offers a family of models of nonholonomic systems.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka